Utilization of voluntary counseling and testing (VCT) services among transexual in Banda Aceh - Yusuf, Nazira; Marthoenis, Marthoenis; Saputra, Irwan; Hermansyah, Hermansyah; Abdullah, Asnawi (Institute of Computer Science (IOCS), 2024)
Indonesia ranks fifth in Asia in terms of high risk of HIV/AIDS. Men who have sex with men (MSM) are 22 times more likely to contract HIV among at-risk populations worldwide. MSM ranks third in the percentage of HIV-positive individuals undergoing HIV testing in Indonesia, at 8.75%. Previous research estimated that there were 30 active transgender sex workers in Banda Aceh and 311 MSM. Voluntary Counseling and Testing (VCT) is one way to detect HIV. However, several factors prevent transgender individuals from utilizing VCT services. The research design used is descriptive quantitative, analyzing VCT utilization among transgender individuals in Banda Aceh in 2021. The sample size in this study is 77 individuals using total sampling technique. Data collection was conducted using a questionnaire. Data analysis involves univariate analysis. t was found that 83.12% of surveyed transgender women are under the age of 35, with 80.52% having a secondary education. 71.43% of them work in salons, and 83.13% identify themselves as Acehnese. Only 50.65% have partners, although 58.44% exhibit a positive attitude towards VCT services. However, 55.84% face stigma and discrimination. Approximately 53.25% of respondents rate VCT facilities positively, but only 54.55% utilize the service. 33.33% have used VCT for 3 years, primarily at health centers, with partner rejection being the main obstacle (34.29%). While 84.42% correctly identify VCT, there are still misunderstandings, such as simultaneous testing and counseling (79.22%). Additionally, only 62.34% are aware of the voluntary nature of HIV testing, and only 50.65% understand the affordability and lifelong treatment of HIV.